Media społecznościowe jako źródło (o)presji związanej z wizerunkiem ciała użytkowników w okresie wczesnej dorosłości - Leksy , Karina; Nowak , Klaudia (Studia Edukacyjne, 2023)
The pressure of an ideal body exerted by silhouettes of models in publicly shared photographs can lead to many adverse effects on the health and well-being of the individual. The article presents the results of the author’s research on the pressure related to body image felt by the surveyed young adults, users of social networking sites, which comes from photos and content present in social media. The research used the diagnostic survey method, using an original online survey questionnaire. The research involved 493 people using social networking sites. The research results indicate that women, more often than men, felt the pressure related to the appearance of their bodies under the influence of social media content. The research results also confirmed a correlation between the time respondents spend on social media and the pressure they feel to improve their body image. The research results demonstrate the need to enhance the digital competencies of young people to equip them with practical tools adapted to the requirements of postmodern visual culture and the information society. However, this task requires updating the means of pedagogical influence, searching for new solutions, and modifying known and proven methods of improving the individual.